2020
DOI: 10.1016/j.ijscr.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiagnostic description of a rare variant of Berrettini anastomois: A case report

Abstract: Highlights In Berrettinni anastomosis, frequently a sensory communicating branch from ulnar nerve supplies digit 3. Despite anatomical evidence of ulnar communicating branch providing sensory supply to digit 2, there are no electrodiagnostic descriptions of the same. Electrodiagnostic findings in a patient with median nerve laceration were suggestive of ulnar sensory innervation of digit 2. Knowledge of existence of these communications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…19 In addition to the electrophysiological evidence of Berrettini's anastomotic communication to the middle finger, 1 7 8 a recent study has reported about Berrettini's anastomotic communication providing sensory supply to index finger too. 20 Therefore, its routine electrophysiological search is recommended before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition to the electrophysiological evidence of Berrettini's anastomotic communication to the middle finger, 1 7 8 a recent study has reported about Berrettini's anastomotic communication providing sensory supply to index finger too. 20 Therefore, its routine electrophysiological search is recommended before surgery.…”
Section: Discussionmentioning
confidence: 99%